The binomial freedom-responsability of those submited to the assisted reproductive techniques: a topic of “living rights” in Peru - Espinoza Espinoza, Juan (2015)
The author explains in his article the legal problems caused it by the assisted reproductive techniques, through the analysis of the jurisprudence of cassation from the Permanent Civil Chamber of the Supreme Court; it makes a legal and reflective analysis of the regulations applicable to the exposed cases in the jurisprudence analyzed, and it shows the lack of peruvian regulations to deal with such problems.